DEFORMATION MONITORING BY GPS AT EMBANKMENT DAMS AND DEFORMATIONANALYSIS - Gokalp, E.; Tasci, L. (Taylor & Francis Ltd, 2009)
Deformation measurements are very important for inspecting huge engineering structures in order to prevent disasters caused by deformation and thus protect national investment. These measurements require the use of very accurate surveying equipment. In particular, the structure of a dam and the physical effects it has on its surroundings need continuous monitoring in order to see if unexpected changes have occurred. If any change is found, remedial work can be performed to protect the structure. The Global positioning System (GPS) meets all of the requirements stated above and therefore, GPS receivers were used in this research. The main aims of this work were the examination of deformation at the crest of the dam caused by water load at different water levels and weight of the dam. Additionally, the study was undertaken to determine whether GPS measurements could reach the accuracy requirements for dam deformation measurements. In order to monitor and examine the deformation, a monitoring network consisting of 6 reference points and 11 object points was established. Measurements were made four times over 2 years using dual frequency GPS receivers with static methods. The measurements were processed and point coordinates were determined. Then differences were calculated between periods and the differences were analyzed by iterative weighted transformation and Fredericton methods to determine the stability of the points. Finally, the results from the two methods were compared and discussed.
Keywords: Deformation; GPS; Monitoring; Point stability